In vivo evaluation of binder jet 3D-Printed monetite, brushite, and octacalcium phosphate: A comparative study for bone regeneration in a rat calvarial defect model - Ticomporn Luangwattanawilai; Faungchat Thammarakcharoen; Autcharaporn Srion; Kasem Rattanapinyopituk; Jintamai Suwanprateeb; Ruedee Hemstapat (PLoS ONE, 2026)
Background Three-dimensional (3D)-printed hydroxyapatite (3DP-HA), fabricated via binder jetting of calcium sulfate-based powders followed by phase conversion, has demonstrated bone regeneration efficacy in both in vitro and in vivo studies. However, the inherently low solubility nature of hydroxyapatite (HA) led to slow resorption, which may impede new bone formation. This study aimed to evaluate the in vivo bone regeneration efficacy of three newly developed resorbable 3D-printed calcium phosphate scaffolds, including brushite (3DP-BRU), monetite (3DP-MO), and octacalcium phosphate (3DP-OCP), fabricated using the similar technology as 3DP-HA. Methods The scaffolds were implanted in a rat calvarial defect model and compared with control groups, including 3DP-HA and two commercial bone grafts: bovine bone graft (BBG) and freeze-dried bone allograft (FDBA). Bone regeneration and material resorption were assessed using micro-computed tomography (micro-CT), histological, and immunohistochemical analyses. Results Micro-CT and histological evaluations demonstrated that 3DP-MO and 3DP-BRU scaffolds significantly enhanced new bone formation and bone cell activities within the defect sites compared with the controls. Furthermore, both 3DP-MO and 3DP-BRU exhibited considerably lower residual graft material compared to the controls, indicating superior resorption characteristics. Conclusion Resorbable 3D-printed calcium phosphate scaffolds, particularly 3DP-MO and 3DP-BRU, exhibit superior resorbability and enhanced bone regeneration compared with conventional materials. These findings highlight their potential as promising biomaterials for clinical application in bone defect repair.